GE_GERICHTE A/2631/2014 vom 1. Dezember 2015 - GE Cour de justice (2015)
BOURSE D'ÉTUDES ; FORTUNE ; REVENU | LFCA.1.al1 ; LFCA.3.al1.letb ; LFCA.11.al1.letb ; LFCA.11.al2.leta ; LFCA.11.letb ; LFCA.11.al.3